2020
DOI: 10.3747/co.27.5621
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in Young Women less than 40 Years of Age with Brain Metastasis from Breast Cancer

Abstract: Background Brain metastasis from breast cancer (bca) in young women is doubly devastating because both quality of life and life expectancy are significantly reduced. With new radiation technology and drugs that have emerged, survival is expected to increase for these young women.Methods Using the oacis and sardo patient databases, we identified 121 patients diagnosed with bca and brain metastasis between 2006 and 2016 at the University of Montreal Hospital Centre. Those patients were divided into Group A, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Age, time of surgery, and the prognostic value of age in terms of survival have been the subject of research with different statements as the aim of research varied or only single cancer entities were analyzed ( 3 , 24 26 ). Nevertheless, two messages can be stated, which are also significantly reflected by our results: First, younger age at time of surgery is correlated with a favored survival ( 26 ), and second, in an older population ( 3 ), tumor remnant in early postoperative MRI is the only risk factor for local in-brain recurrence. With a median age of 64.0 years (range 18–93) of the analyzed population, maximally selected log rank statistics revealed a significant cutoff for the age of 67 years ( p < 0.001), whereby 439/704 (62.4%) patients are ≤67 years.…”
Section: Discussionmentioning
confidence: 99%
“…Age, time of surgery, and the prognostic value of age in terms of survival have been the subject of research with different statements as the aim of research varied or only single cancer entities were analyzed ( 3 , 24 26 ). Nevertheless, two messages can be stated, which are also significantly reflected by our results: First, younger age at time of surgery is correlated with a favored survival ( 26 ), and second, in an older population ( 3 ), tumor remnant in early postoperative MRI is the only risk factor for local in-brain recurrence. With a median age of 64.0 years (range 18–93) of the analyzed population, maximally selected log rank statistics revealed a significant cutoff for the age of 67 years ( p < 0.001), whereby 439/704 (62.4%) patients are ≤67 years.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Mustillo et al emphasize that survival was higher in women <40 years with initial brain metastasis. 26 However, it must be remembered that metastasis is an important predictor of severe and poor survival, but prognosis will be determined by metastatic pattern and molecular subtype.…”
Section: Discussionmentioning
confidence: 99%
“…We also reviewed study which reported that HER2 did not have an prognostic in uence on HR-positive young BC [27]. Age has been de ned as an independent risk factor for survival in BC patients [9,28,29]. Xu et al reported a 95.2% 5-year OS in patients under age 60 (mainly composed of post-menopausal women ) [30].…”
Section: Discussionmentioning
confidence: 99%